Nucleus Pearl Coating Process of Freshwater Mussel Anodonta woodiana (Unionidae) - SATA YOSHIDA SRIE RAHAYU; DEDY DURYADI SOLIHIN; WASMEN MANALU; RIDWAN AFFANDI (HAYATI Journal of Biosciences, 2013)
The limiting factor which is a weakness of sea water pearl production are high costs, the risk of major business failures and a long coating time. From the issue of freshwater pearls appear to have prospects of alternative substitution for sea water pearl. This present study aimed to evaluate effect of loads (the number and diameter nucleus) on freshwater pearl coating process and the number and size of the appropriate nucleus diameter, to produce the optimum coating thickness of half-round pearls. The research consists of experimental implantation of 2, 4, and 6 nucleus number per individual mussel was maintained by the method stocked in hapa in bottom waters. Observation method and factorial randomized block design used in the study of the influence of the load to the successfulness of  pearl coating and the pearl layer thickness. The results showed that A. woodiana can be utilized as a producer of freshwater pearls. In addition, the number of optimum nucleus that can be attached to the mussel A. woodiana was 2 grains/individuals with a diameter of 10 mm. Shells implanted with the optimum nucleus diameter and number of pearls produced the highest layer thickness of 17 mm after 9 months cultivation. This result was good enough compared with the layer thickness of sea water pearl production after the same cultivation time.